2010
DOI: 10.1186/1472-6882-10-52
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity screening of Bangladeshi medicinal plant extracts on pancreatic cancer cells

Abstract: BackgroundThere has been a long standing interest in the identification of medicinal plants and derived natural products for developing cancer therapeutics. Our study focuses upon pancreatic cancer, due to its high mortality rate, that is attributed in part to the lack of an effective chemotherapeutic agent. Previous reports on the use of medicinal plant extracts either alone or alongside conventional anticancer agents in the treatment of this cancer have shown promising results. This work aims to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 30 publications
1
31
0
Order By: Relevance
“…Results are mean values ± SD of independent experiments performed in triplicate. natural products (Desai et al, 2008;Sigstedt et al, 2008;George et al, 2010;Dai et al, 2011;Shynu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are mean values ± SD of independent experiments performed in triplicate. natural products (Desai et al, 2008;Sigstedt et al, 2008;George et al, 2010;Dai et al, 2011;Shynu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Natural products are a rich resource of cancer chemotherapy drugs, and primarily target rapidly cycling tumor cells, experimental studies demonstrated that many naturally occurring agents and plant extracts have anticancer potential in a variety of bioassay systems and animal models, having relevance to human diseases (Aziz et al, 2003), thus the longstanding interest in the identification of medicinal plants and derived natural products for developing cancer therapeutics increased steadily (Yu et al, 2001;George et al, 2010;Dai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these plant-derived anticancer agents have been discovered through large-scale screening programs (Pezzuto 1997). Several plant extracts and plant-derived products have been shown to induce apoptosis in many human tumors (George et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is one of the most life-threatening diseases with more than 200 different types. Due to lack of effective drugs, expensive cost of chemotherapeutic agents and their side effects, cancer can be a cause of death (George et al 2010). Plants have been used in the treatment of cancer for ages.…”
Section: Introductionmentioning
confidence: 99%